A review of causes of delay in construction projects - Al-Mohammad, Mohammad; Omar, Jamaludin (Science Publishing Corporation, 2018)
Time is one of the keys by which project success can be measured. However, delay in construction projects remains a common occurrence. This paper attempts towards reviewing past literature on causes of delay in different types of construction. The most common methods adopted by researchers for causes of delay identification were presented. This review also discussed the groups causing delay based on the source of delay. The top five delay factors related to contractor, owner and consultant have been discussed within each category. This paper revealed that previous researches are regarded as the main source for causes of delay identification. Moreover, questionnaire and the relative importance index are the most frequent methods for collecting data and ranking delay factors, respectively. Contractor, owner and consultant groups are the highest frequent groups utilized for categorization. Furthermore, causes of delay related to contractor and owner are of great importance. While consultant group and its relevant causes have shown lesser importance relatively.